THE USE OF AUGMENTED REALITY IN THE EDUCATIONAL PROCESS - Alexander A. Kurganov; Rinat G. Gilvanov; Lyudmila A. Zyatikova (International Journal of Advanced Studies, 2023)
Background. The relevance of the research is determined by the tarnsformation in the modern educational process of the role of students’ attitudes, subjective norms and perceived behavioral control in the implementation of augmented reality applications for digital learning. The article is devoted to the study of the question: “How does conducting lectures through an extended application increase students’ confidence and affect their attitudes and subjective norms?”